2004
DOI: 10.1080/09712119.2004.9706502
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dietary Natural Zeolite andSaccharomyces cerevisiaein Counteracting Aflatoxicosis in Broiler Chicks

Abstract: Modirsanei, M., Khosravi, A.R., Kiaei, S.M.M., Bozorgmehri Fard, M.H., Gharagozloo, M.J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…This result is consistent with those reported by Marchioro et al (2013) that aflatoxin increased digestive enzymes of broilers, but did not improve their growth performance, indicating that absorption is affected by existence of mycotoxins in the diet. The improving role of 0.05% E-GM to neutralize the deleterious effects of mycotoxicosis on performance has been previously reported by Aravind et al (2003) and Modirsanei et al (2004). On the contrary, Liu et al (2011) failed to improve the chickens' performance by 0.05% E-GM supplementation.…”
Section: Discussionmentioning
confidence: 72%
“…This result is consistent with those reported by Marchioro et al (2013) that aflatoxin increased digestive enzymes of broilers, but did not improve their growth performance, indicating that absorption is affected by existence of mycotoxins in the diet. The improving role of 0.05% E-GM to neutralize the deleterious effects of mycotoxicosis on performance has been previously reported by Aravind et al (2003) and Modirsanei et al (2004). On the contrary, Liu et al (2011) failed to improve the chickens' performance by 0.05% E-GM supplementation.…”
Section: Discussionmentioning
confidence: 72%
“…Zeolites (12,16), bentonites (7,11,26), and yeast/esterified glucomannan (1,4,6,15) were opted for because of their effect on reducing aflatoxin absorption from the gastrointestinal tract. Some studies have showed that the best method for decontamination is biological degradation by yeast and yeast components, which can remove aflatoxin under mild conditions, without using harmful chemicals or causing noticeable losses in nutritive value and palatableness of the feed (21,30).…”
Section: Introductionmentioning
confidence: 99%
“…In animal nutrition, clinoptilolites are used mainly to protect animals against mycotoxin intoxications (Skalicka and Makoova 1999;Skalicka et al 2000;Rizzi et al 2003;Modirsanei et al 2004;Desheng et al 2005), to eliminate heavy metals (Boranić 2000) and radionuclides (Poschl and Balas 1999;Vitorovic et al 2002;Branislava and Gordana 2004), as well as to prevent digestive tract diseases, to improve utilization of feed nutrients, and to improve hygienic and sanitary conditions in animal housing facilities (Meisinger et al 2001;Melenova et al 2003). They have a positive effect on the production performance in pigs (Veldman and Aar 1997;Papaioannou et al 2004) and in poultry (Amon et al 1997;Olver 1997).…”
mentioning
confidence: 99%